Understanding Motivation, Empowerment and Sustainability Outcomes of Women Homestay Entrepreneurs in West Malaysia. A Preliminary Analysis. - Osman, Intan; Ahmad, Noor Hazlina; Ahmad, Zainal Ariffin; Husin, Azrina; Abu Bakar, Saridan; Tanwir, Nur Diyana (2010)
The participation of women in the homestay industry is a growing phenomenon; yet research in this area is limited especially in Malaysia.